RHYTHM DISTURBANCES AND OBSTRUCTIVE SLEEP APNEA - Івчина, Надія (SWorldJournal, 2022)
Atrial fibrillation (AF) is the most common arrhythmia. Obstructive sleep apnea syndrome has become a more common pathology in recent decades. AF in combination with obstructive sleep apnea syndrome is a common and urgent problem today. According to some